Android Based Employee Absence and Leaving Application Information System - Baenil Huda; Shofa shofia Hilabi; Maya Rahayuningsih (Information System; Universitas Buana Perjuangan Karawang, 2021)
Attendance in general is the recording of employee attendance and is one aspect of assessment in a company. The purposes of this study are finding out how employees can apply for leave and how to design and build an Android-based attendance system application. Data collection methods that used in this research include observation, interviews and literature study. The system development method that will be used is the System Development Life Cycle (SDLC) model of the Waterfall. With this system, employees and companies will be helped in the problem of absence and leave. The company will get accurate, fast and precise data in decision making.